The central element of the synaptonemal complex in mice is organized as a bilayered junction structure - Hernández-Hernández, Abrahan (2017)
The synaptonemal complex transiently stabilizes pairing interactions between homologous chromosomes during meiosis. Assembly of the synaptonemal complex is mediated through integration of opposing transverse filaments into a central element, a process that is poorly understood. We have, here, analyzed the localization of the transverse filament protein SYCP1 and the central element proteins SYCE1, SYCE2 and SYCE3 within the central region of the synaptonemal complex in mouse spermatocytes using immunoelectron microscopy. Distribution of immuno-gold particles in a lateral view of the synaptonemal complex, supported by protein interaction data, suggest that the N-terminal region of SYCP1 and SYCE3 form a joint bilayered central structure, and that SYCE1 and SYCE2 localize in between the two layers. We find that disruption of SYCE2 and TEX12 (a fourth central element protein) localization to the central element abolishes central alignment of the N-terminal region of SYCP1. Thus, our results show that all four central element proteins, in an interdependent manner, contribute to stabilization of opposing N-terminal regions of SYCP1, forming a bilayered transverse-filament–central-element junction structure that promotes synaptonemal complex formation and synapsis.